Pengaruh Model Guided Discovery Learning Berbantuan Media Simulasi PhET Terhadap Kemampuan Berpikir Kreatif Peserta Didik - Syahrial Ayub; Baiq Nabila Saufika Zainuri; Aris Doyan (LAMBDA : Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2022)
The research is aimed to examine the influence of a guided discovery learning model assisted by PhET simulation media on students' creative thinking skills. The type of research used is quasi-experiment research with a nonequivalent control group design. The population used is the students of class X IPA SMAN 1 Kediri. Sampling using a saturated sampling technique with all members of the population as a sample, where class X IPA 1 is the experimental class and X IPA 2 is the control class. The technique of data analysis was carried out by a polled variance t-test. The results of the t-test indicate that the value of is greater than (2.03) at a significant level of 5% so that Ha is accepted, which means that the creative thinking ability of students on the subject of momentum and impulse has increased after being given treatment. The highest increase occurred in the class using a guided discovery learning model assisted by PhET simulation media. Based on the results of the study, it can be concluded that there is an influence of the guided discovery learning model assisted by PhET simulation media on students' creative thinking skills